Praecordial surface mapping after exercise in evaluation of propranolol for angina pectoris. Issue 4 (April 1980) - Fox, K; Selwyn, A; Oakley, D; Jonathan, A; Shillingford, J
Abstract : The effect of propranolol on ST depression in the praecordial 16 lead electrocardiogram was observed in 52 patients before and after treatment, both at rest and after exercise. In a further 20 patients exercise tests repeated on separate days two months apart showed that the technique gave reproducible results. A variable relation between symptomatic relief and praecordial exercise-induced ST segment depression was noted. Use of a single fixed-position chest lead (V5) was shown to be less accurate. The relief of symptoms alone is probably an inadequate guide to the success of medical treatment, which should control not only angina but also the manifestations of ischaemia on the praecordial electrocardiogram.